2005
DOI: 10.1177/0146167204271550
|View full text |Cite
|
Sign up to set email alerts
|

Putting Stereotype Content in Context: Image Theory and Interethnic Stereotypes

Abstract: Two studies apply intergroup image theory to better understand divergent interethnic images and to highlight the important role of intergroup context and perceived intergroup relations in shaping the content of social stereotypes. Image theory hypothesizes that specific interethnic stereotypes arise from specific patterns of perceived intergroup competition, relative power, and relative cultural status. Results from surveying Black, White, and Native Americans' appraisals of intergroup relations and reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 15 publications
(22 reference statements)
2
86
1
2
Order By: Relevance
“…Participants were asked to respond to a series of questions regarding their perceptions of refugees, including three items that assessed an enemy image (e.g., ''Refugees would take advantage of any efforts on our part to cooperate, and they would even try to exploit us''), and three items that assessed a barbarian image (e.g., ''Refugees are crude, unsophisticated, and willing to cheat to get their way'') with possible responses on each ranging from 1 (strongly disagree) to 7 (strongly agree). Because factor analysis indicated that the enemy and barbarian images were not distinct, we calculated average scores across all six items (Cronbach's a = .87; see Soc Just Res (2008) 21:4-25 9 also Alexander et al, 2005). Higher scores indicate increasing dehumanization of refugees.…”
Section: Dehumanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked to respond to a series of questions regarding their perceptions of refugees, including three items that assessed an enemy image (e.g., ''Refugees would take advantage of any efforts on our part to cooperate, and they would even try to exploit us''), and three items that assessed a barbarian image (e.g., ''Refugees are crude, unsophisticated, and willing to cheat to get their way'') with possible responses on each ranging from 1 (strongly disagree) to 7 (strongly agree). Because factor analysis indicated that the enemy and barbarian images were not distinct, we calculated average scores across all six items (Cronbach's a = .87; see Soc Just Res (2008) 21:4-25 9 also Alexander et al, 2005). Higher scores indicate increasing dehumanization of refugees.…”
Section: Dehumanizationmentioning
confidence: 99%
“…As a result, the ingroup is perceived to be justified in taking action against the enemy group. The barbarian image, which often loads on the same factor as the enemy image (see Alexander, Brewer, & Livingston, 2005), includes perceptions of an outgroup as ruthless, crude, unsophisticated, and willing to cheat to get its way. Support for these images has been found in several studies across a variety of groups and, of relevance to the current research, perceived incompatibility of goals has been found to strongly predict both the enemy and barbarian images (e.g., Alexander et al, 1999Alexander et al, , 2005.…”
mentioning
confidence: 99%
“…If aggregate personality differences across cultural groups can lead to aggregate behavioral differences, then these variations in behavior might then elicit stereotype-relevant attributions. Such attributions would represent a kind of kernel of truth that could reinforce national stereotypes (Eysenck, Humphery & Eysenck, 1980;Lynn & Martin, 1995;McCrae & Terracciano, 2005), as one among many mechanisms by which cultural stereotypes may arise (for other possible mechanisms, see Linssen & Hagendoorn, 1994;Alexander, Brewer, & Livingston, 2005).…”
Section: Nonverbal Accents and Cultural Stereotypesmentioning
confidence: 99%
“…For instance, Jackson and colleagues (1996) have shown that stereotypes of Asians varied greatly. As Alexander, Brewer, and Livingston (2005) have suggested, there is a recent heightened interest in the actual content of specific stereotypes, and several competing theories of stereotype content have been developed (Eagly, Wood, & Diekman, 2000;Fiske, Cuddy, Glick, & Xu, 2002;Johannesen-Schmidt & Eagly, 2002). Second, in these studies it is difficult to examine the experiences that have led to the acquisition of a specific stereotype.…”
mentioning
confidence: 99%